Separate and unequal : judicial rhetoric and women's rights - Chng, Huang Hoon (Discourse approaches to politics, society, and culture, 2002)
This book argues for a multidisciplinary approach to the study of the language of judges with respect to the issue of gender discrimination. Drawing its inspiration from Dell Hymes' socially constituted linguistics, the author examines the language of the judicial opinions of four U.S. Supreme Court cases addressing social and legal discrimination against women. Through a linguistic analysis that is informed by a Foucauldian and feminist perspective, this book addresses the complex issues of the power of judges and ideologies, the politics of language use, and feminist contributions to the sub.